Cardiovascular Risk Factors Among Older Adults With Long‐Term Spinal Cord Injury. Issue 1 (16th January 2019) - Jörgensen, Sophie; Hill, Mattias; Lexell, Jan
Abstract: Background: Individuals with spinal cord injury (SCI) now live longer, which increases the risk of cardiovascular disease. Knowledge of cardiovascular risk factors amenable to intervention are therefore needed to support their healthy aging. Objective: To describe the occurrence of cardiovascular risk factors among older adults with long‐term SCI and investigate the association with sociodemographics and injury characteristics. Design: Cross‐sectional descriptive cohort study. Setting: Home settings. Participants: In total, 123 individuals (71% men, injury levels C1–L5, American Spinal Injury Association Impairment Scale A–D), mean age 63 years, mean time since injury 24 years. Methods: Data from the Swedish Aging with Spinal Cord Injury Study (SASCIS), collected through interviews and assessments during home visits and from medical records. Main Outcome Measures: Anthropometric measurements, blood pressure, fasting plasma glucose and blood lipids, and data on cardiovascular comorbidity and tobacco use. Results: One third had a previous diagnosis of hypertension, and 55% presented with a blood pressure ≥ 140/90 mm Hg at the time of assessment. Sixteen percent had a history of diabetes and in 15% fasting glucose levels were ≥ 7 mmol/L. Dyslipidemia was present in 76%, whereas 16% had prediagnosed dyslipidemia. Mean body mass index (BMI) was 27 kg/m 2 and mean waist circumference was 101 cm. When SCI‐adjusted BMI cut‐off values were used, 93% were considered overweight (BMI ≥22 kg/m 2 ), and 60% had a waist circumference associated with cardiometabolic risk. A total of 16% smoked regularly. The median number of cardiovascular risk factors was 3. No significant associations were found between the total number of risk factors and sociodemographics and injury characteristics. Conclusions: The high occurrence of cardiovascular risk factors among older adults with long‐term SCI can pose additional consequences to their health. Regular assessments and interventions targeting cardiovascular risk in this population are therefore warranted. Further research is needed to identify modifiable factors associated with their risk profile. Level of Evidence: III